Bloodshot [videorecording (DVD)] - Heughan, Sam, 1980-; González, Eiza, 1990-; Riley, Talulah, 1985-; Pearce, Guy, 1967- (Sony Pictures Home Entertainment, 2020)
Ray Garrison is a soldier recently killed in action and brought back to life as a superhero by the RST Corporation, which now controls Ray's body, mind, and memories. With an army of nanotechnology in his veins, he's an unstoppable force, stronger than ever and able to heal instantly. Faced with the reality that he can't believe anything -- even his own thoughts -- he's on a mission to discover his true reality.